The Realization of Adverb –Ly in English Sentences - Huda, Masrul (Tamaddun Life, 2022)
The objective of the study is to find the realization of Adverb -ly in sentences. This study is descriptive qualitative which is carried out through the process of providing data, the data analysis stage, and the systematic stage of presenting the results of data analysis. In the data analysis stage, the data that has been collected is sorted according to their respective categories and given further descriptions and explanations. The result shows 1. The position of the adverb –ly can be placed in three positions, the beginning of the sentence (before the subject), the middle of the sentence (before the verb), and the end of the sentence (after the main clause). 2. Adverb –ly in a sentence can modify if it is in the form of a phrase, in the construction of comparative sentences, modifying 'however' to open a clause, modifying 'how' in an exclamation sentence, and modifying 'so' which is followed by the subject. and clauses. 3. Based on its semantic meaning the adverb -ly can have several meanings: point of view, as an emphasizer, as a maximiser, as a booster, as a minimizer, and as instrument. The research answers the realization of the adverb –ly can be in various places in English sentences, but the semantic meaning can be different. The present study implicates on adverbs having distinct semantic orientations, which provides natural reference materials for teaching and learning English in the EFL context.